2020
DOI: 10.1167/tvst.9.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retinal Function and Pathology After Intravitreal Injection of Povidone-Iodine and Polyvinyl Alcohol-Iodine in Rabbits

Abstract: Citation: Shimada H, Kato K, Ishida K, Yamaguchi T, Shinoda K. Evaluation of retinal function and pathology after intravitreal injection of povidone-iodine and polyvinyl alcohol-iodine in rabbits. Trans Vis Sci Tech. 2020;9(5):5, https://doi.org/10. 1167/tvst.9.5.5 Purpose: This study compared intraocular toxicity of intravitreally injected povidoneiodine (PI) and polyvinyl alcohol-iodine (PAI) in rabbits. Methods:In each rabbit, 0.1 mL of PI or PAI solution was injected intravitreally into one eye and sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…For this reason, we disinfect the eyelids, eyelashes, and conjunctival fornix with at least 10 mL of 0.25% povidone-iodine before draping; irrigate the ocular surface with several ml of povidone-iodine after placing the solid blade lid speculum; wait for 30 s; and then perform intravitreal injection while the povidone-iodine remains on the ocular surface. According to a study performed using rabbit eyes, there is no retinal damage associated with washing the ocular surface with 0.25% povidone-iodine during intravitreal injection [41]. After injection, the ocular surface is again disinfected with several ml of povidone-iodine to prevent endophthalmitis [42].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we disinfect the eyelids, eyelashes, and conjunctival fornix with at least 10 mL of 0.25% povidone-iodine before draping; irrigate the ocular surface with several ml of povidone-iodine after placing the solid blade lid speculum; wait for 30 s; and then perform intravitreal injection while the povidone-iodine remains on the ocular surface. According to a study performed using rabbit eyes, there is no retinal damage associated with washing the ocular surface with 0.25% povidone-iodine during intravitreal injection [41]. After injection, the ocular surface is again disinfected with several ml of povidone-iodine to prevent endophthalmitis [42].…”
Section: Discussionmentioning
confidence: 99%
“…When cells were exposed to stable solutions of PVP carrier alone or I 2 , toxicity was solely caused by I 2 (Figs 1C-E and S1A-C). Above a threshold of free I 2 at 0.5 mM, elemental iodine is an irreversible respiratory poison, likely explaining topical toxicity such as retinal degradation (Shimada et al, 2020), and clinical sudden cardiovascular and metabolic collapse upon high-level systemic exposure (Glick et al, 1985;Kanakiriya et al, 2003;Ramaswamykanive et al, 2011), confirmed in animal models (Lores et al, 1981;Song et al, 2018). To translate these findings to a 3D environment, calcein AM-labelled epithelial spheroids were exposed to PVP-I or I 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Former authors found only a range between 0.005% and 0.1% effective, as it caused only minor membrane damage ( Van den Broek et al, 1982 ). Others found the safe concentration range to vary with cell type, such as <0.033% for the retina ( Shimada et al, 2020 ), <0.05% for corneal endothelial cells ( Jiang et al, 2009 ), and <0.05% for corneal epithelial cells ( Swift et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, electroretinography (ERG) and histologic examinations of the retina were performed to verify that both 0.1% and 0.3% PI were tolerable. Furthermore, 0.025% PI-balanced salt solution (BSS) PLUS (Alcon Laboratories, Fort Worth, TX) is a bactericidal drug when used as an irrigation solution for vitrectomy in eyes with endophthalmitis (21). IVI of 1.25% PI followed by vitrectomy using 0.025% PI irrigation for treating endophthalmitis was proved to be effective (22).…”
Section: Discussionmentioning
confidence: 99%